Heminthiasis in a Wild Rats (Rattus sp.) in Surabaya - Hemasayu Nirmala Putri; Budiarto Budiarto; Arimbi Arimbi; Lucia Tri Suwanti; Kusnoto Kusnoto; Soeharsono Soeharsono (Journal of Parasite Science (JoPS), 2019)
The research was done to investigated and find out whether in the rat’s (Rattus sp.) body in Surabaya contained zoonotic helminth.This research used 31 rats taken from North Surabaya, South Surabaya, East Surabaya, West Surabaya and Central Surabaya, regardless of gender and age. 1 sample from Mulyosari, 3 samples from Bratang, 7 samples from Pegirian, and 20 samples came from Keputran. The result of 31 samples of rat’s digestive organs examine using a surgical method showed positive resulth of the presence of Hymenolepis diminutain the intestine and 5 positive samples were Capillaria hepatica, and then 25 positive samples were Taenia taeniaformis obtained from rat liver organs. From exploration using a microscope, 27 samples showed positive result in the presence of Capillaria hepatica’s eggs. Helminth found in this research are Hymenolepis diminuta, Taenia taeniaformis. and Capillaria hepatica which are zoonotic.